Distributed controllers multi-granularity security communication mechanism for software-defined networking. (February 2018) - Shang, Fengjun; Li, Yan; Fu, Qiang; Wang, Wenkai; Feng, Jiangfan; He, Li
Abstract: For the multi-domain software defined network (SDN), different controllers are not able to directly communicate with each other due to the different distances among control planes. Therefore, the exchange of information among different domains is generally unsecure. The main contribution of this paper can be summarized into two parts. Firstly, architecture of multi-granularity security controller is proposed, which includes a basic control module and a multi-granularity security customized module. Secondly, a secure communication mechanism is proposed for distributed controller, where a prototype of this mechanism is implemented. In particular, this mechanism can make use of the border switch as inter-domain agents, where special packets are used by the controller to send messages to the secure tunnel. A two-step authentication of the controller can be provided by inter-domain agents and digital certificates. The experimental results demonstrate that the distributed controller secure communication mechanism is capable of effectively improving the security of SDN domain.